2006
DOI: 10.1093/rpd/nci529
|View full text |Cite
|
Sign up to set email alerts
|

LiF:Mg,Cu,P glow curve shape dependence on heating rate

Abstract: The glow curve shape of LiF:Mg,Cu,P (MCP) material is studied in this research. The study is focused on the effects of the heating rate on the dosimetric peaks. Different configurations of dosemeters (chips, cards and powder) are studied. The shifting of the dominant dosimetric peak is observed and analysed. The curves are deconvoluted using the new Harshaw Glow Curve Analyser (GCA) program. Results of the study are presented, as well as possible explanations as to the observed effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 6 publications
2
6
0
Order By: Relevance
“…Table 1 shows the shifts in the temperatures of glow peaks with increasing heating rates. These were considered qualitatively similar to those reported by Luo et al (2006) and Stadtmann et al (2006) for LiF:Mg,Cu,P. For the 0.8 mm thick TLD pellets, the sample to sample variation in the peak temperature (not in the TL response) increased with heating rate due to the contact heating.…”
Section: Methodssupporting
confidence: 85%
See 2 more Smart Citations
“…Table 1 shows the shifts in the temperatures of glow peaks with increasing heating rates. These were considered qualitatively similar to those reported by Luo et al (2006) and Stadtmann et al (2006) for LiF:Mg,Cu,P. For the 0.8 mm thick TLD pellets, the sample to sample variation in the peak temperature (not in the TL response) increased with heating rate due to the contact heating.…”
Section: Methodssupporting
confidence: 85%
“…1 shows typical glow curves of 0.8 mm thick LiF:Mg, Cu,Si pellets recorded 30 min after the irradiation by 90 Sr-90 Y beta rays by using heating rates of 1, 10 and 30 • C s −1 . The glow curve structure is similar to that of LiF:Mg,Cu,P (Luo et al, 2006). At a heating rate of 1 • C s −1 , there are three well separated glow peaks at 105, 154 and 205 • C. To keep the nomenclature the same as that normally used for LiF:Mg,Cu,P, these peaks for LiF:Mg,Cu,Si were denoted in an ascending order of the temperature as peaks 2, 3 and 4.…”
Section: Methodsmentioning
confidence: 64%
See 1 more Smart Citation
“…Pradhan [3] reported that the glow-peak areas of LiF TLD-700 ribbons and LiF:Mg,Cu,P increase for the heating rates in the range from 1 K/s to 20 K/s. Meanwhile Luo et al [9] reported that peaks 3+4 in LiF:Mg,Cu,P remain almost unchanged at 90% of the total integral. Recently Pradhan et al [10] reported that in LiF:Mg,Cu,Si the main glow peak did not exhibit any significant reduction with increasing heating rate in the range from 1 to 30 K/s.…”
Section: Iii2 Effect Of Heating Rate On Tl Glow-peaksmentioning
confidence: 99%
“…However, the TL response strongly depends on heating rate, an important parameter in the TL measurements. Influence of the heating rate on TL glow curve has been the object of study by different authors [1][2][3][4][5][6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%